“Bog here, marshland there”:tensions in co-producing scientific knowledge on solar geoengineering in the Arctic - Mettiäinen, Ilona; Buck, Holly; MacMartin, Douglas; Ricke, Katharine L. (Environmental Research Letters, 2022)
Solar geoengineering has been suggested as a means to cool the planet and ameliorate climate impacts in the Arctic. However, few studies approach this idea from the viewpoint of Arctic communities. We explore the substantive rationale for public engagement with solar geoengineering research, including the premises that: (a) evaluation of local impacts by communities can generate better knowledge about what modeling results mean; and (b) ideas and questions surfaced in public discussions can contribute to and shape scientific research. We convened focus groups in Finnish Lapland, conducted scientific analysis of climate model output on albedo modification based upon the discussions, and returned a year later to discuss the results. The increased granularity of scientific information highlighted the limited scientific basis for decisions, which turned the discussions back towards questions of ethics and justice. We conclude that while there are serious limitations to global public decision-making on climate intervention, in the absence of formal governance, co-producing research could act as one de facto form of governance.